Analisis Konsep Panggilan dan Visi dalam Kepemimpinan Kristen - Sinah, Pace Aprisal; Sinah, Pace Aprisel (STT Pelita Dunia, 2025)
Essential Christian leadership is a sacred grace and responsibility that functions as a representation of Christ, rooted in two pillars: Divine Calling and Prophetic Vision. Calling is the ontological foundation that emphasizes character integrity and service, answering the question